Alternative Resolution Mechanism in Regional Election Disputes - Sukaca (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study is motivated by the high intensity of disputes in the implementation of Regional Head Elections (Pilkada) in Indonesia, which frequently generate political conflicts and legal uncertainty. Regulatory changes, particularly through Law Number 10 of 2016, have significantly influenced the enforcement system and dispute resolution mechanisms in Pilkada. This research aims to analyze the model of informal dispute resolution in Pilkada and its role in strengthening the electoral justice system. The study employs a normative juridical method with a descriptive-analytical approach, examining primary, secondary, and tertiary legal materials related to Pilkada dispute resolution. The findings reveal that, in addition to formal judicial mechanisms, there are alternative or informal mechanisms such as unilateral withdrawal, amicable settlement, mediation, and arbitration that function as complementary instruments to the formal system. These mechanisms promote faster and more efficient resolutions while encouraging win–win solutions to prevent political escalation. It is concluded that informal dispute resolution plays a strategic role in reinforcing procedural and substantive justice and in supporting the realization of democratic and fair regional elections.